Philippine banking almanac, 1995 (Manila Venture Unlimited, 1995)
An impressive encyclopedia of information on Philippine banks and financial institutions and related information. It provides useful reference and guide in determining which type of financial intermediary would best serve the needs of businessmen and entrepreneurs.
Keywords: Banks and banking -- Philippines -- Handbooks, manual, etc; Banks and banking -- Philippines -- Directories; Banks and banking -- History. -- Philippines; Financial institutions -- Philippines